2011
DOI: 10.2478/v10014-011-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive responses of spring and winter wheat cultivars to chilling and acclimation treatments

Abstract: Photosynthesis and antioxidant defense system were investigated under chilling stress without (Ch, and with acclimation (AcCh, 14-4 ºC) in winter (Sabalan) and spring (Zagros) wheat (Triticum aestivum L.) cultivars. Maximum quantum efficiency of photosystem II and CO 2 assimilation rate decreased in AcCh 'Zagros' but not in 'Sabalan', and in contrast, an increase in non-photochemical quenching was observed in 'Sabalan' but not in 'Zagros'. Reduction of leaf starch content was observed in both cultivars while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Various studies showed a similar response to cold stress in wheat [61], strawberries [62], and barley [63]. Hajiboland and Habibi [64] reported that in cold-treated seedlings, the activity of SOD increased significantly, while in the acclimated seedlings, SOD activity did not differ from the control.…”
Section: Enzymatic Antioxidantsmentioning
confidence: 84%
See 2 more Smart Citations
“…Various studies showed a similar response to cold stress in wheat [61], strawberries [62], and barley [63]. Hajiboland and Habibi [64] reported that in cold-treated seedlings, the activity of SOD increased significantly, while in the acclimated seedlings, SOD activity did not differ from the control.…”
Section: Enzymatic Antioxidantsmentioning
confidence: 84%
“…Higher POD and SOD activity probably suggest their possible role in mitigating adverse environmental damage. Hajiboland and Habibi [64] reported a slight increase in CAT activity in both wheat cultivars under chilling temperatures with and without acclimation. In contrast, POD activity increased in spring wheat cultivar but not in winter wheat by both temperature treatments.…”
Section: Plant Stress Responses and Defense Mechanismsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this connection, many authors have been reported that low temperature stimulated the scavenging of H 2 O 2 by both enzymatic antioxidants CAT and APx (Hajiboland & Habibi, 2011;Mohammadian et al, 2012;Sorour, 2014). In contrast, Kang & Saltveit (2001) and Ping et al (2012) have reported that chilling stress resulted in a significant decrease of CAT activity in cucumber seedlings and rubber colenes respectively, while, Galli et al (2009) showed that APx activity did not show a clear trend during the cold storage of pawpaw fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Under heat stress, plants contain numerous enzymatic ROSscavengers antioxidants, including superoxide dismutase (SOD), catalase (CAT), peroxidase (POx), ascorbate peroxidase (APx), glutathione peroxidase (GPx) and glutathione reductase (GR) as well as non enzymatic antioxidants such as ascorbate, glutathione and phenolics (Kang & It has been reported that chilling stress enhanced SOD activity in several plants including cucumber (Kang & Saltveit, 2002), wheat (Hajiboland & Habibi, 2011) and citrus fruit (Mohammadian et al, 2012). reported that CAT activity significantly increased during chilling stress, while Ping et al (2012) reported a decrease of CAT activity in rubber tree clones seedlings in response to chilling stress.…”
Section: Introductionmentioning
confidence: 99%